Effect of Pre-habilitation on Functional Recovery after Total Knee Arthroplasty: A Randomized Controlled Trial - Muhammad, Riaz; Afsar, Sardar Sohail; Rehman, Yaqoob Ur; Uddin, Afaq (Journal of Neonatal Surgery, 2025)
Background: The most common degenerative disease is osteoarthritis of the knee, which has become more common in recent years. It is a major source of work-related impairment in Western nations, where its incidence among adults surpasses 20%. Pain management and improving joint function are the main goals of the treatment approach for knee osteoarthritis. Objective: To determine the effect of Pre-habilitation on Functional Recovery after Total Knee Arthroplasty Methodology: The current randomized controlled trial study was carried out at the orthopaedic department, Nowshera Medical College and Qazi Hussain Ahmad Medical Complex Nowshera. The study duration was one year from March 2023 to March 2024 after taking approval from the ethical committee of the hospital. In the current study, a total of 120 patients were enrolled. They were divided into control group and preoperative rehabilitation group. Sixty patients were placed in each group. The intervention group received a structured preoperative rehabilitation program that included supervised exercise sessions designed to increase cardiovascular fitness, joint flexibility, and lower limb strength. The program took place three times a week for the four weeks before to surgery. The control group received standard preoperative treatment, and no structured exercise regimen was put in place. Six weeks and three months after surgery, mobility was evaluated using the Timed Up and Go (TUG) test. To measure post-surgery pain, VAS was used. The quality of life was evaluated concurrently using the Knee Injury and Osteoarthritis Outcome Score (KOOS). Data was collected at the beginning, six weeks, and three months after surgery. SPSS version 24 was used for data analysis. Results: In the current study, a total of 120 patients were enrolled. They were divided into control group and preoperative rehabilitation group. Sixty patients were placed in each group. In the baseline characteristics no statistical significant difference was observed between the two groups (p˃0.05). At the 3- month follow-up, the rehabilitation group continued to exhibit improvement in functional mobility, with a time difference of 12.6 (2.01) seconds compared to 15.3 (1.99) seconds in the control group (p=0.005). At six weeks and three months after surgery, the rehabilitation group had less pain, as indicated by the VAS score. In the rehabilitation group, the mean (SD) duration of hospital stay was 3.7 (0.4) days, whereas in the control group it was 4.3 (0.99) days (p = 0.001). Conclusion: Our research concluded that preoperative rehabilitation significantly increases functional mobility, reduces pain, and enhances quality of life in patients undergoing total knee arthroplasty